Evaluation of Ozone Therapy Effectiveness by the Red Cell Distribution Width/Albumin Ratio - Betos Koçak, Meryem; Nas, Mehmet Akif; Yılmaz Kartal, ideal Beraa (The European Research Journal, 2026)
Objective: Ozone is an inorganic gas utilized for medical purposes. Ozone therapy has gained increasing popularity in recent years and is employed in the treatment of chronic diseases associated with inflammation. The red cell distribution width/albumin ratio (RAR) has recently emerged as an inflammatory marker. The aim of this study was to evaluate the efficacy of ozone therapy in patients with spinal pain and to investigate the effect of ozone therapy on inflammation through changes in the RAR value.Methods: This prospective pilot study was conducted in a pre- and post-treatment design on patients with spinal pain. In addition to demographic data, visual analog scale (VAS) scores and RAR values were recorded before and after ozone therapy. All patients underwent major ozone autohemotherapy. Data were analyzed using the SPSS software.Results: During the study period, 93 patients presented to the ozone therapy unit. After applying the exclusion criteria, 66 patients were included in the analysis. The mean pre-treatment VAS score was 6.74±1.53, while the mean post-treatment VAS score was 4.08±1.54 (P